2019
DOI: 10.1186/s41938-019-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic efficacy of the chitinolytic bacteria: Aeromonas hydrophila isolated from Siwa Oasis, Egypt

Abstract: Thirty-four bacterial isolates were isolated from soil samples collected from the North Western Coast and a water sample collected from brackish water at Siwa Oasis, Matrouh Governorate, Egypt. Only six isolates showed chitinase activity when screened on colloidal chitin agar medium. The highest chitinolytic activity was achieved by a bacterial isolate labeled as A.S. This isolate was identified as Aeromonas hydrophila based on analysis of 16S rRNA gene sequence and morphological, physiological, and biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Aeromonas hydrophila was isolated from brackish water sample collected from Siwa Oasis, Egypt. The pathogenic activity of this bacterial species against Galleria mellonella, its potentiality for chitinase production and the LC50 value of the crude chitinase were determined (Korany et al, 2019). According to the later authors, the LC50 of crude chitinase was found to be 135.0 U/mg protein and had been used through this study.…”
Section: Source Of Crude Chitinase Enzymementioning
confidence: 97%
“…Aeromonas hydrophila was isolated from brackish water sample collected from Siwa Oasis, Egypt. The pathogenic activity of this bacterial species against Galleria mellonella, its potentiality for chitinase production and the LC50 value of the crude chitinase were determined (Korany et al, 2019). According to the later authors, the LC50 of crude chitinase was found to be 135.0 U/mg protein and had been used through this study.…”
Section: Source Of Crude Chitinase Enzymementioning
confidence: 97%
“…From 85 isolates only 27 isolates (35.29%) showed vivid zone of chitin hydrolysis. Korany et al (Korany et al, 2019) reported that among the thirty four isolates only four isolates produced zones of clearance (hydrolysis) on chitin agar medium. Similarly Ajayi et al ( 2016) had isolated 36 chitinolytic isolates but selected 24 on the basis of highest chitnolytic index.…”
Section: Functional Group and Vibration Modesmentioning
confidence: 99%